Intrinsic Organic Semiconductors as Hole Transport Layers in p–i–n Perovskite Solar Cells. Issue 4 (28th December 2021) - Susic, Isidora; Zanoni, Kassio P. S.; Paliwal, Abhyuday; Kaya, Ismail C.; Hawash, Zafer; Sessolo, Michele; Moons, Ellen; Bolink, Henk J.
Abstract : Thin polymeric and small‐molecular‐weight organic semiconductors are widely employed as hole transport layers (HTLs) in perovskite solar cells. To ensure ohmic contact with the electrodes, the use of doping or additional high work function (WF) interlayer is common. In some cases, however, intrinsic organic semiconductors can be used without any additive or buffer layers, although their thickness must be tuned to ensure selective and ohmic hole transport. Herein, the characteristics of thin HTLs in vacuum‐deposited perovskite solar cells are studied, and it is found that only very thin (<5 nm) HTLs readily result in high‐performing devices, as the HTL acts as a WF enhancer while still ensuring selective hole transfer, as suggested by ultraviolet photoemission spectroscopy and Kelvin probe measurements. For thicker films (≥5 nm), a dynamic behavior for consecutive electrical measurements is observed, a phenomenon which is also common to other widely used HTLs. Finally, it is found that despite their glass transition temperature, small‐molecule HTLs lead to thermally unstable solar cells, as opposed to polymeric materials. The origin of the degradation is still not clear, but might be related to chemical reactions/diffusion at the HTL/perovskite interface, in detriment of the device stability. Abstract : Herein, vacuum‐deposited p–i–n perovskite solar cells employing very thin films of intrinsic organic semiconductors as the hole transport layers is studied. When no dopants nor high work function interlayers are used, the devices show a dynamic electrical behavior before reaching efficient steady state operation. Devices with small molecules are not thermally stable, as opposite to polymer transport layers in the same configuration.